2023
DOI: 10.1101/2023.07.21.550109
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic epidemiology of EuropeanAspergillus fumigatuscausing COVID-19-associated pulmonary aspergillosis in Europe

Abstract: The opportunistic fungus Aspergillus fumigatus has been found to cause coinfections in patients with severe SARS-CoV-2 virus infection, leading to COVID-19-associated pulmonary aspergillosis (CAPA). The CAPA all-cause mortality rate is approximately 50% and may be complicated by azole-resistance. Genomic epidemiology can help shed light on the genetics of A. fumigatus causing CAPA including the prevalence of alleles that are associated with azole-resistance. Here, a population genomic analysis of 21 CAPA isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…Recent research has revealed that strains of A. flavus, the second largest cause and one of the main agents of serious comorbidities, including Aspergillosis; also causing co-infections in patients with severe infection by the SARS-CoV-2 virus, leading to pulmonary aspergillosis associated with COVID-19 (Mariscal et al, 2023;Simmons et al, 2023) were tested after exposure to the same azoles agricultural products had the MIC (Minimum Inhibitory Concentration) for drugs of the same class, posaconazole, voriconazole and itraconazole increased, showing that agricultural pesticides can, in fact, reduce the effectiveness of antifungals used in the clinic (Meireles et al, 2019).…”
Section: Isolation Of Filamentous Fungimentioning
confidence: 99%
“…Recent research has revealed that strains of A. flavus, the second largest cause and one of the main agents of serious comorbidities, including Aspergillosis; also causing co-infections in patients with severe infection by the SARS-CoV-2 virus, leading to pulmonary aspergillosis associated with COVID-19 (Mariscal et al, 2023;Simmons et al, 2023) were tested after exposure to the same azoles agricultural products had the MIC (Minimum Inhibitory Concentration) for drugs of the same class, posaconazole, voriconazole and itraconazole increased, showing that agricultural pesticides can, in fact, reduce the effectiveness of antifungals used in the clinic (Meireles et al, 2019).…”
Section: Isolation Of Filamentous Fungimentioning
confidence: 99%